Evaluation of post-keratoplasty status with a portable and smartphone-attachable smart eye camera - Yuto Yukari; Yuki Senoo; Takahiko Hayashi; Toshiki Shimizu; Yusuke Hara; Hiroki Nishimura; Shintaro Nakayama; Eisuke Shimizu; Satoru Yamagami (PLoS ONE, 2025)
Purpose To evaluate the efficacy of the smart eye camera (SEC), a portable smartphone-attachable camera, in assessing eyes following lamellar corneal transplantation. Methods This retrospective study included consecutive patients who underwent lamellar corneal transplantation between December 1 st 2023 and August 31 st 2024. Postoperative evaluations were performed using the SEC and a slit-lamp microscope. All images from the two devices were evaluated by two corneal specialists in a blinded fashion to determine the amount of air or gas in the anterior chamber, and the presence of pupillary block and graft detachment. Sensitivity, specificity, and interrater agreement were calculated. Results A total of 26 eyes from 23 patients (12 males and 11 females, mean age: 68.7 ± 15.2 years) were included in this study. Indications for lamellar keratoplasty included endothelial dysfunction (11 eyes were treated with Descemet membrane endothelial keratoplasty and 9 with Descemet stripping automated endothelial keratoplasty), as well as corneal opacity (3 eyes were treated with deep anterior lamellar keratoplasty). Regarding the amount of air or gas in the anterior chamber, the two raters had consistent judgments using the SEC (intraclass correlation coefficient = 0.817 [95% confidence interval: 0.616, 0.918]). A difference in pupillary block identification was found between the two examiners using the SEC, with a Kappa coefficient of 0.646. Neither examiner was able to identify the presence of graft detachment using the SEC. Conclusions The smartphone-attachable SEC was useful in the evaluation of air/gas volume and pupillary block but not for detecting graft detachment.